Optical properties and sequence information of tin-centered conjugated microporous polymers - Uptmoor, Andrea Christina; Elbert, Sven; Wacker, Irene; Schröder, Rasmus R.; Mastalerz, Michael; Freudenberg, Jan; Bunz, Uwe H. F. (Chemistry - a European journal, 2018)
We synthesized conjugated microporous polymers (CMPs) based on tetrakis(4-ethynylphenyl)stannane and diiodobenzene as tectons, using Sonogashira couplings under different conditions. Through variation of the reaction conditions (catalysts, bases and solvents), appearance, surface area and emission properties of the formed CMPs were significantly altered. Wet-chemical, acid-mediated digestion and analysis of the resulting struts of these otherwise insoluble networks give insight into the molecular setup.